SELECTION OF A LEADER FOR A COMPANY BY USING PRIORITIZATION METHODS OF ANALYTIC HIERARCHY PROCESS AN ILLUSTRATION - prasad, voruganti shyam; Kousalya, P (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
This paper aims at selection of a leader for a company (whose founder is about to retire) with one of the popular decision making techniques. Analytic Hierarchy Process is an approach to decision making that involves structuring multiple criteria into hierarchy. There are several methods to calculate the priority vectors. Three prioritization methods are used to select a leader among three alternatives and four criteria. It is observed that Dick stands first in ranking and Tom stands second and Harry stands third in rankings. Consistency Ratio (C.R) also calculated for all pair-wise comparison matrices and analyzed.